Design of an Information System for Testing the Blood Characteristics on Increasing the Impact of Vibration using a Prototype “Blood Shaker Machine” - Jessica Juan Pramudita; Edy Susanto; Luthfi Rusyadi (Genius Journal, 2022)
Objective: The general purpose of this research is to design an information system based on the application of blood characteristics testing on platelets to increase the impact of vibration by using a "Blood Shaker Machine" examined through a Haematology Analyzer (HA) and Peripheral Blood Smear (SADT) at any changes in the increase in vibration. Method: The method used in this study is to design an application-based system on the "Blood Shaker Machine" and test the increase in vibration on changes in blood quality both in terms of the number and morphology of the platelets. Result: Significant changes in the morphology of erythrocytes and platelets in the 10 Hz vibration group for 15 minutes also indicated a change in the quality of blood cells, both erythrocytes and platelets.  Conclusion: There is a significant difference in erythrocyte morphology changes between before and after being vibrated at 10 Hz with a p value of 0.014 and There is a significant difference in platelet morphology between before and after being vibrated at 10 Hz with a p value of 0.000.